Exploring Tourists' Experience in Cinema-Induced Tourism through Sentiment Analysis Approach: Case of Ouarzazate Film Attractions - TAIBI, Moulay Abdellah; HANBALI, Raja; IFLAHEN, Fatima-Zohra (Journal of Environmental Management and Tourism, 2024)
This research aims to explore tourists’ experiences in movie-induced tourism in the region of Ouarzazate, the hub of the cinematographic industry in Morocco and Africa to come up with managerial implications that can improve the tourist experience in this region. A sentiment analysis approach was applied to TripAdvisor reviews in English on the three main filming facilities and attractions: Atlas and CLA studios and the film museum in Ouarzazate. The method combined topic modeling and lexicon-based algorithms; an approach based on Natural Language Processing using a Python toolkit to investigate prevailing sentiment among visitors of these touristic sites. The result of our study showed that tourists generally have a positive sentiment towards the region of Ouarzazate. However, the desert still dominates as the primary aspect that attracts tourists to the region, while cinema is a secondary attraction to the majority of tourists.  The study is one of the first studies to reflect on the potential of Cinema Induced Tourism in Ouarzazate, Morocco, one of the attractive destinations for tourists and filmmakers, which, despite its potential, does not figure among cinema-induced tourism destinations in the literature.